SMOKE FREE AREA (SFA) DISTRICT REGULATION SUPPORT FOR ESTABLISHMENT OF A CHILD FRIENDLY SCHOOL (CFS) IN KULON PROGO DISTRICT - Agri Aryoko; Oktavian Denta; Iud Karnaningrum; Arvicha Fauziah; Theodola Baning (Universitas Airlangga, 2021)
ABSTRACTFollowing the Child-Friendly School (CFS) Guidelines made by the Deputy for Child Development, Ministry of Women Empowerment and Child Protection (2015), one of the components that must be fulfilled is a commitment to make schools a Smoke-Free Area (SFA). Kulon Progo has District Regulation No. 5 of 2014 concerning SFA, thus it can be used as a commitment by a school guide, making it an SFA. The results of interviews with the District Social Service for Women's Empowerment and Child Protection Office stated that CFS currently remains at the initiation stage. Efforts should be made to create comfortable learning conditions for children with the support of the SFA District Regulation in the formation of CFS in Kulon Progo Regency. Analysis of the implementation monitoring checklist/compliance with District Regulation No. 5/2014 concerning SFA in 2020 which is carried out by the SFA supervision task force. Descriptive analysis method by looking at trends based on the proportion of the 10 variables used. The results of the data study show that 89.5% have been exposed to the socialization of District Regulations, 52.6% have a supervisory task force, 86.8% have installed SFA signs at the Entrance, 100% have a smoking ban warning installed, 23.7% has a place specifically for smoking, 10.5% found an ashtray in the building, 7.9% found cigarette butts, 2.6% found cigarette advertisements, 5.3% found cigarette sellers, 7.9% smoked people. From the data analysis, it is known that 81.58% have complied with SFA. However, this compliance is not optimal. This is indicated by the high percentage of availability of designated smoking areas in schools and ashtrays, cigarette butts, cigarette advertisements, cigarette sellers, and smoking people found. Schools should have a zero percentage in these variables; thus, they are not fully committed as a condition for the formation of CFS. It is necessary to optimize the application of District Regulations to create a smoke-free school environment as evidenced by not providing smoking places in schools, not allowing cigarette advertisements, smoking outside, and imposing sanctions for non-smoking violators in the school environment. Keywords: Support, Smoke-Free Area (SFA), Child Friendly Schools, Kulon Progo